(untitled) (Journal of Pedagogical Inventions and Practices, 2021)
Storytelling is the original form of teaching and has the potential of fostering emotional intelligence and help the child gain insight into human behavior. Storytelling also promotes language learning by enriching learners’ vocabulary and acquiring new language structures